Quality of life and comorbidities associated with Dravet syndrome severity: a multinational cohort survey. (6th October 2017) - Lagae, Lieven; Brambilla, Isabella; Mingorance, Ana; Gibson, Eddie; Battersby, Alysia
Abstract : Aim: To test the hypothesis that higher seizure burden in Dravet syndrome is associated with increased comorbidities and lower quality of life (QoL) in a large cohort of patients with Dravet syndrome and their caregivers in Europe. Method: An extensive survey of caregivers of patients with Dravet syndrome on experiences of diagnosis, seizure burden, management, social and financial impact, and health services use was administered online in 10 languages. Results: The survey received 584 unique responses from caregivers of paediatric (83%) and adult (17%) patients with Dravet syndrome (aged <1–48y). Despite broadly following current treatment guidance, less than 10% of patients were seizure free in the previous 3 months. Nearly all (99.6%) patients aged 5 years or older experienced at least one or more motor, speech, learning, or behavioural impairment. High seizure frequency was related to more reports of emergency treatment, comorbidities, and a lower QoL (as measured by the standardized instrument EQ‐5D‐5L). If not diagnosed at the first instance, the majority (83%) of adults, but less than 20% of 6‐ to 11‐year‐olds were diagnosed after 4 or more years. Interpretation: Patients with Dravet syndrome with the highest current seizure frequency suffer from more comorbidities and have a lower QoL. Therefore, more effective antiepileptic treatments are needed. What this paper adds: The survey captured about 15% of all patients with Dravet syndrome in Europe. Less than 10% of patients had current seizure freedom. Patients with a high current seizure burden have more comorbidities and lower quality of life. What this paper adds: The survey captured about 15% of all patients with Dravet syndrome in Europe. Less than 10% of patients had current seizure freedom. Patients with a high current seizure burden have more comorbidities and lower quality of life. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=NZhDw0DLMec&feature=youtu.be